Scrutinizing the Impacts of Grammarly Application on Students’ Writing Performance and Perception - Suryanto, Suryanto; Habiburrahim, Habiburrahim; Akmal, Saiful; Zainuddin, Zamzami; Safrul, Muhammad Safwan; Hanani, Fatayatul (Jurnal Ilmiah Peuradeun, 2024)
This research explored the impact of the Grammarly application on students’ writing performance and perceptions, particularly during the thesis writing stage. Writing is a complex cognitive process requiring strategic planning, organization, grammar, and vocabulary skills. The study focused on students majoring in English Language Education at Ar-Raniry State Islamic University, specifically those in their ninth semester from the 2018 cohort. A purposive sample of 42 students, all at the thesis writing stage and users of Grammarly, was selected from a total of 127. Additionally, three lecturers, serving as thesis supervisors, were randomly selected for interviews from a pool of 20. The research employed both qualitative and quantitative methods, using survey questionnaires and interviews for data collection. Results indicated that Grammarly was a beneficial tool for students, significantly aiding in thesis writing and reducing the time spent on checking grammatical errors. The surveys revealed unanimous student agreement on Grammarly’s positive impact on their writing process. Interviews with lecturers supported this, noting an improvement in the quality of theses written by students who used Grammarly. This study underscored the effectiveness of Automated Writing Evaluation (AWE) tools like Grammarly in enhancing students’ writing skills and outcomes.